Quantitative Analysis of Closed Porosity in Direct Resin Composites: A Micro-CT Study on the Influence of Material Type - Mangoush, Enas; Lassila, Lippo; Vallittu, Pekka K.; Garoushi, Sufyan (United Kingdom, 2026)
Aim: This study aimed to evaluate and compare the average pores size and closed porosity levels in different types of resin composites using micro-computed tomography (micro-CT).
Materials and methods: Ninety specimens (2.5 mm × 4 mm × 4 mm) were prepared using 15 different materials divided into 15 groups (n = 6/group). Groups were either conventional packable (Filtek Universal Restorative and G-aenial A'chord), conventional flowable (CLEARFIL MAJESTY ES Flow, G-aenial Flo X, and G-aenial Universal Injectable), bulk fill flowable (SDR flow+ and Filtek Bulk Fill Flowable Restorative), dual-cure (Gradia Core and CLEARFIL DC Core Plus), or fiber-reinforced composites (Nova Pro Flow, Fibrafill DENTIN, everX Flow with either Dentin or Bulk shade, and everX Posterior), in addition to one glass hybrid material (EQUIA Forte HT Fil). All specimens were scanned using a micro-CT machine (Bruker Skyscan 1272), and analyzed for the average size, volume percentage, and distribution of closed porosities. Data was analyzed using Shapiro-Wilk for normality, followed by two-way ANOVA with Tukey's HSD for group comparisons. Pearson correlation assessed the relation between the average size and the percentage of closed pores.
Results: The results revealed significant differences in closed porosity levels among the tested groups. Filtek Universal Restorative exhibited the lowest porosity (0.049%), while Fibrafill DENTIN had the highest (4.78%) and the largest average pore size (0.996 mm³). In contrast, A'chord had the smallest average closed pore size (0.017 mm³) (p < 0.05). When the composites were categorized into flowable and packable variants, a significant difference (p < 0.05) was observed in the average percentage of closed pores, with flowable composites showing a lower porosity (0.31%) compared to packable composites (1.25%). Conclusion: The findings highlight the influence of material type on porosity formation, with larger pore sizes correlating with higher closed porosity percentages.